Effects of Population Redistribution on Greenhouse Gas Emissions: A Case Study of South Korea. (April 2016) - Lee, Daegoon; Cho, Seong-Hoon; Roberts, Roland K.; Lambert, Dayton M.
The objective of this research was to analyze how population dynamics affect greenhouse gas (GHG) emissions. We assessed the effects of population redistribution resulting from the South Korean government's decentralization efforts on GHG emissions. Simulation results suggest that the direction of change in total GHG emissions depends on the share of the population redistributed from higher to lower population density regions. If the entire redistributed population of 877, 000 persons expected from the government's decentralization project were from the Seoul Area, annual carbon dioxide emission (CO2 e) would increase by 1.72 percent to 2.25 percent compared to benchmark levels. Alternatively, more balanced migration between higher and lower population density regions, that is, 65 percent of the 877, 000 persons from higher-density locations to lower-density destinations and 35 percent from lower-density to higher-density regions, decreases CO2 e by 1.68 percent to 2.50 percent.